Plots of epiphany : prison-escape in Acts of the Apostles - Weaver, John B. (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2004)
Past scholarship on the prison-escapes in the Acts of the Apostles has tended to focus on lexical similarities to Euripides' Bacchae, going so far as to argue for direct literary dependence. Moving beyond such explanations, the present study argues that miraculous prison-escape was a central event in a traditional and culturally significant story about the introduction and foundation of cults - a story discernable in the Bacchae and other ancient texts. When the mythic quality and cultural diffusion of the prison-escape narratives are taken into account, the resemblance of Lukan and Dionysian narrative episodes is seen to depend less on specific literary borrowing, and more on shared familiarity with cultural discourses involving the legitimating portrayal of new cults in the ancient world.